Visual Outcomes and Complications in Pediatric Traumatic Cataract Surgery at a Tertiary Care Hospital: Doi: 10.36351/pjo.v42i1.2115 - Naveed Malik, Sarah; Sumaira Altaf; Rabeeah Zafar; Najia Uzair; Summaya Anjum (Pakistan Journal of Ophthalmology, 2025)
Purpose: To evaluate visual outcomes of traumatic cataract surgery in pediatric patients and identify preoperative, per operative and postoperative complicationsof management. Study Design: Quasi experimental study. Place and Duration of Study: Department of Pediatric Ophthalmology and Strabismus, Al-Shifa Trust Eye Hospital, Rawalpindi from April 2024 to September 2024. Methods: This study included 61 children (≤16 years) who underwent surgery for traumatic cataract. Patients with any pre-existing ocular pathology or follow-up <6 months were excluded. Demographic data, type of trauma, timing of surgery, Itype of intraocular lens (IOL), and complications were recorded. Visual acuity (VA) was measured at baseline and at one week, three months, and six months, converted to logMAR for analysis. Statistical tests included repeated measures ANOVA and Spearman correlation. Results: Mean age was 8.37 ± 3.62 years; 70.4% were male. Blunt and penetrating injuries were equally distributed. Foldable in-the-bag IOLs were most common (35.4%). Preoperative complications of trauma were present in 88.5%, most frequently visual axis opacification (39.3%). Postoperatively, 52.5% had no complications; others developed astigmatism (29.5%), anterior uveitis (18.0%), or IOL dislocation (9.9%). Mean LogMAR VA improved from 2.09 to 0.80 in 6 months (p < 0.001). Better outcomes were observed in older children and those without complications. Timing of surgery and trauma type did not significantly affect final VA. Conclusion: Pediatric traumatic cataract surgery offers favorable visual outcomes. Age and complication profile significantly affects prognosis. Timely intervention, individualized rehabilitation, and vigilant postoperative monitoring are essential for optimizing results and minimizing long-term sequelae.